2006
DOI: 10.1089/ars.2006.8.1391
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum: Folding, Calcium Homeostasis, Signaling, and Redox Control

Abstract: The endoplasmic reticulum (ER) plays a major role in regulating synthesis, folding, and orderly transport of proteins. It is also essentially involved in various cellular signaling processes, primarily by its function as a dynamic Ca(2+) store. Compared to the cytosol, oxidizing conditions are found in the ER that allow oxidation of cysteine residues in nascent polypeptide chains to form intramolecular disulfide bonds. However, compounds and enzymes such as PDI that catalyze disulfide bonds become reduced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
399
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(414 citation statements)
references
References 259 publications
10
399
0
5
Order By: Relevance
“…48 Consistent with these previous reports, we confirmed that inhibition of ROS with NAC, a widely used antioxidant, significantly attenuated the cytotoxicity of aldosterone. Oxidative stress is a known inducer of ER stress 49 and autophagy. 50 As expected, the current study revealed the enhanced effect of aldosterone-induced podocyte ER stress and autophagy was inhibited by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…48 Consistent with these previous reports, we confirmed that inhibition of ROS with NAC, a widely used antioxidant, significantly attenuated the cytotoxicity of aldosterone. Oxidative stress is a known inducer of ER stress 49 and autophagy. 50 As expected, the current study revealed the enhanced effect of aldosterone-induced podocyte ER stress and autophagy was inhibited by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…ROS participate in oncogenic signaling and elevated ROS levels are a salient feature of aggressive cancers (17,18). Disturbances in the delicate ROS balance can lead to protein misfolding, accumulation of dysfunctional proteins, and activation of cellular stress responses (36). In accordance, STEAP1 silencing provokes transcriptional and posttranscriptional adaptations of oxidative stress responses comprising the redox, chaperone, endopeptidase, and UPS.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins are several redox enzymes such as peroxiredoxins and superoxide dismutases, which are dysregulated in a large cohort of cancers (15,34). Moreover, endosomal redox stress response proteins (35,36) were identified including T-complex chaperones, heat shock proteins, protein-disulfide isomerases as well as co-chaperones. Furthermore, we identified mediators of posttranscriptional mRNA processing such as heterogeneous nuclear ribonucleoproteins, THO complex proteins, and eukaryotic translation initiation factors (Supplementary Table S4).…”
Section: Knockdown Of Steap1 Inhibits Proliferation Invasion Anchormentioning
confidence: 99%
“…Another possibility is that reactive oxygen species (ROS) may cause ER stress through generation and accumulation of oxidized proteins [11,17]. The ER appears to be particularly sensitive to such modifications [18][19][20][21], as its molecular environment has a high oxidizing redox potential, specialized in protein folding and disulfide bond formation [18,22,23]. Finally, ROS could directly damage proteins of the ER folding machinery, such as ER chaperones, and induce an accumulation of misfolded proteins and consequent UPR activation.…”
Section: Page 33 Of 65mentioning
confidence: 99%